1974
DOI: 10.1017/s0022112074001479
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the viscous sublayer and the adjacent wall region in a turbulent channel flow

Abstract: Hot-film anemometer measurements have been carried out in a fully developed turbulent channel flow. An oil channel with a thick viscous sublayer was used, which permitted measurements very close to the wall. In the viscous sublayer between y+ ≃ 0·1 and y+ = 5, the streamwise velocity fluctuations decreased at a higher rate than the mean velocity; in the region y+ [lsim ] 0·1, these fluctuations vanished at the same rate as the mean velocity.The streamwise velocity fluctuations u observed in the viscous subl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
127
4

Year Published

1975
1975
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(158 citation statements)
references
References 11 publications
27
127
4
Order By: Relevance
“…The existence of the streaks is, however, well established (see e.g. Kline et al 1967;Kim, Kline & Reynolds 1971;Eckelmann 1974). Note that the difference between horseshoe, hairpin and lambda vortices is largely a function of Reynolds number (Head & Banyopadhyay 1981), with low-Reynolds-number structures having a more horseshoe-like appearance.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of the streaks is, however, well established (see e.g. Kline et al 1967;Kim, Kline & Reynolds 1971;Eckelmann 1974). Note that the difference between horseshoe, hairpin and lambda vortices is largely a function of Reynolds number (Head & Banyopadhyay 1981), with low-Reynolds-number structures having a more horseshoe-like appearance.…”
Section: Introductionmentioning
confidence: 99%
“…One may try to do this by increasing the viscous length scale, /uy either by reducing,u, by lowering the free stream speed or by increasing, V, as Eckelmann (1974) has done in his oil channel measurements. Both these methods reduce the Reynolds number of the flow and make the wall region very thick compared to the boundary layer thickness.…”
Section: W W Willmarthmentioning
confidence: 99%
“…Eckelmann (1970Eckelmann ( , 1974, Kreplin, Eckelmann and Wallace (1974), Kreplin (1976) and ri're recently Blackwelder and Eckelmann (1977a) made correlation measurements in conjunction with an investigation of the structure of the near-wall region. The thick viscous sublayer of the oil channel allowel measurements very close to the wall.…”
Section: Space-time Correlationmentioning
confidence: 99%
“…Consider first a turbulent boundary layer flowing over an erodible boundary. Several recent studies 1967;Corino and Brodkey, 1969;Grass, 1971;Eckelmann, 1974) have shown that flow in a turbulent boundary layer near rough and smooth boundaries is characterized by ej'ection of low-momentum fluid parcels away from the boundary and inrush of high-momentum fluid parcels toward the boundary, This phenomenon has been termed bursting; the threedimensional picture is one of eddies bursting from the bed, being entrained in the flow near the bed, and stretching in a downstream sense (Kim et al, 1971). It has further been suggested (Grass, 1971) that this process of momentum exchange is primarily responsible for turbulence production near the boundary,…”
Section: Conceptual Model For Erosion Of Fine-grained Sedimentsmentioning
confidence: 99%